2022
DOI: 10.3390/app12042221
|View full text |Cite
|
Sign up to set email alerts
|

Midpalatal Suture Density as a Function of Sex and Growth-Pattern-Related Variability via CBCT Evaluations of 392 Adolescents Treated with a Rapid Maxillary Expander Appliance

Abstract: Background and objectives. This paper aimed to evaluate the changes in mean bone density values of the midpalatal suture (MPS) in 392 young patients treated with a rapid palatal expander (RPE) appliance, depending on sex and vertical and sagittal skeletal patterns. Materials and Methods. Evaluations were performed using a low-dose protocol for cone beam computed tomography scans at T0 (preoperative) and T1 (1 year after the beginning of the therapy). The region of interest was used to calculate bone density in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The combination of CBCT scans with virtual setups also avoids potential root displacements outside the original bone structure. Therefore, in line with other studies, we observed the achievement of desired skeletal and aesthetic outcomes following orthognathic surgery associated with clear aligners [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…The combination of CBCT scans with virtual setups also avoids potential root displacements outside the original bone structure. Therefore, in line with other studies, we observed the achievement of desired skeletal and aesthetic outcomes following orthognathic surgery associated with clear aligners [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…The purpose of this case report was to evaluate the development and the compensation mechanisms of the mandibular asymmetry in a growing male patient using cone beam computed tomography (CBCT) after treatment with RPE and FR-3 ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary transverse deficiency (MTD or maxillary hypoplasia) is a common problem that affects the normal development of the maxillofacial complex. Therefore, early diagnosis and correction of MTD are essential to achieve a normal transverse skeletal relationship between the maxilla and mandible ( 21 ). There are three types of MPS disjunction: RPE (with dental support), miniscrew-assisted rapid palatal expansion (MARPE) with skeletal support, and surgically assisted rapid palatal expansion (SARPE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to their design, the dental-craniofacial and cervical-postural systems, as well as the neuromuscular system, alveoli, TMJs (temporomandibular joint system), soft tissues, salivary glands, and mandibular and maxillary bases, are all reflected in the functional activity of EAs [21,25,42,[49][50][51][52][53][54].…”
Section: Design Principles Of Easmentioning
confidence: 99%